Actitudes de los profesionales médicos frente a la interrupción voluntaria del embarazo en el Hospital Regional de Loreto - 2022 - Inga Villacorta, Félix Anthony (2023)
Objectives: Evaluate attitudes of medical professionals towards the voluntary termination of pregnancy at the Regional Hospital of Loreto - 2022. Methods: Descriptive study and cross-sectional design, which had 70 medical professionals as study population, directly contracted at the Regional Hospital of Loreto, 2023. Obtaining as results: the doctors are young and male; Being the majority Catholic and with children, the attitude of the doctors towards the voluntary interruption of pregnancy was predominantly positive, of them the General Medicine doctors had a more positive attitude towards the voluntary interruption of pregnancy. In multivariate analysis, physicians younger than 37 years were more likely to have a positive attitude toward voluntary termination of pregnancy compared with those older than 37 years. Physicians with religion were less likely to have a positive attitude towards voluntary termination of pregnancy compared with those without religion. Physicians with less than 10 years of service were also more likely to have a positive attitude toward voluntary termination of pregnancy. Conclusions: Younger medical professionals, those without religion, and those with fewer years of medical professional service were found to be more likely to have positive effect attitudes toward voluntary termination of pregnancy compared with their older, religious, and older counterparts. of service.